265 Pool fencing bylaws and drowning rates among children. (1st September 2016) - Clemens, Tessa; Rotondi, Michael; Tamim, Hala; Macpherson, Alison
Abstract : Background: The majority of fatal drownings in Canada occur in natural bodies of water; however private backyard pools are consistently the most common setting where children under 5 years of age drown. A number of studies conducted primarily in Australia and the United States have provided evidence that pool fencing reduces the risk of drowning among children. No long term analysis of pool fencing and municipal bylaws as a factor affecting the risk of childhood drowning in Canada has been published. Methods: Using a multi-level ecologic study design, the drowning death rate in Ontario municipalities with isolation fence and gate legislation was compared to that in municipalities with less or no legislation. Individual level descriptive analysis was conducted using data collected from files at the Ontario Provincial Coroner's office for all children under the age of 5 who suffered drowning deaths in private backyard pools over a fifteen year period. Drowning death rates were calculated per 100 000 population. Denominators for rates were yearly estimates of population under the age of 5 for each municipality. Poisson regression methods were used to estimate relative risks and 95% confidence intervals. Additionally, univariate analysis was conducted and descriptive statistics were reported to summarise the characteristics of childhood backyard pool drownings. Results: During the study period, 54 children under the age of 5 drowned in a private backyard pool in Ontario. The highest death rate was found among 2 year olds (0.9 per 100 000) and the male to female ratio was 3.5:1. The majority of children (61%) drowned after accessing an unobstructed pool directly from the residence. (Results of Poisson regression to be updated). Conclusions: The results of the study demonstrate the need for isolation fencing bylaws that do not allow direct access from the building, and do not allow fences to be "grandfathered" under existing legislation.